Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Industri Barang dan Konsumsi Yang Terdaftar di Bursa Efek Indonesia - Gregorius Paulus Tahu; Ni Ketut Sri Wulandari; I Wayan Widnyana; Dominicius Djoko Budi Susilo (CV. Ulil Albab Corp, 2024)
In companies that have short-term goals and long-term goals, the short-term goal is that the company can get the maximum possible profit by utilizing the resources owned by the company while the long-term goal is to maximize the value of the company. The purpose of this study was to determine the effect of profitability, leverage, and firm size on firm value in the consumer goods and industry listed on the Indonesia Stock Exchange. The object of research used in this study is Profitability, Leverage and Firm Size on Firm Value in the Goods and Consumption Industry Listed on the Indonesian Stock Exchange. The sampling method in this study was to use a purposive sampling technique, where the samples were taken from 30 consumer and goods industry companies listed on the Indonesia Stock Exchange. Data analysis techniques using multiple linear regression analysis, multiple correlation analysis, determination analysis and t test. The results of this study indicate that profitability has a positive effect on firm value in the consumer goods and industry listed on the Indonesia Stock Exchange. Leverage has no effect on firm value in the consumer goods and industry listed on the Indonesia Stock Exchange. Company size has a positive effect on firm value in the consumer goods and industry listed on the Indonesia Stock Exchange.